The Influence of Providing Health Promotion about Anemia Through Educational Video Media Towards The Improvement of Knowledge for Grade VIII Stundent at SMPN 7 Palangka Raya - Dea Savitri; Melisa Frisilia; Stefanicia Stefanicia (PROMOTOR, 2026)
According to data from the Central Kalimantan Provincial Health Office, in 2024, there were 463 recorded cases of anemia among adolescent girls aged 12 to 16 years. A lack of knowledge about anemia can negatively affect teenage health, such as decreased immunity, reduced physical fitness, stunted growth and development, lower motivation to learn, and academic performance. If not addressed early, anemia poses risks of complications during future pregnancy and childbirth, such as bleeding, and can contribute to increased maternal and infant mortality rates. Objective: This study aims to identify the effect of health promotion about anemia through educational video media on increasing knowledge among 8th-grade female students at SMPN 7. Method: This research used a pre-experimental design with a one-group pretest-posttest type of research. The sample in this research amounted to 42 respondents. The sampling technique used was proportional sampling. The data analysis used the Wilcoxon test. Result: This research showed the results of the Wilcoxon test, obtained (p value = 0.000 or p <0.05). This means there was a significant influence on providing health promotion about anemia through educational video media towards improving knowledge for grade 8 students at SMPN 7 Palangka Raya. Conclusion: The health promotion using educational video media has proven to be effective in increasing understanding of adolescent girls because it could encourage adolescent girls to be more focused on receiving information, could increase learning interest, and help adolescent girls understand health material more comprehensively.